2012
DOI: 10.4103/0970-9290.104954
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of the regional micro-push-out bond strength of custom-made resin post system with a prefabricated resin post: An in vitro study

Abstract: Within the limitations of the study, amongst all the four groups tested, custom-made resin post luted with self-etch system (CMPR-SE) showed higher micro-push-out bond strength values in all regions when compared to the other groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Push-Out bond strength test possesses a good approximation of the bond strength than the conventional shear test. Push-Out fracture develops corresponding to dentin-bonding interface (23,24) , which makes it a true shear test and simulates the clinical condition more closely. Group IV with the largest diameter showed the highest Push-Out bond strength value, which may mean that decreasing the cement space between the post and root dentin wall increases the Push-Out bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…The Push-Out bond strength test possesses a good approximation of the bond strength than the conventional shear test. Push-Out fracture develops corresponding to dentin-bonding interface (23,24) , which makes it a true shear test and simulates the clinical condition more closely. Group IV with the largest diameter showed the highest Push-Out bond strength value, which may mean that decreasing the cement space between the post and root dentin wall increases the Push-Out bond strength.…”
Section: Discussionmentioning
confidence: 99%
“…The Micro-Push-Out (µPO) test is employed to measure the bond strength of luted fibre posts. It is a modification of the PO test, and it involves disks of a radicular dentin specimen with thickness less than or equal to 1 mm 2 [ 34 , 35 ]. Castellan et al ., [ 36 ] reported that a µPO approach and µTBS resulted in higher values than traditional pull-out and push-out methods.…”
Section: Types Of Bond Strength Testing Methodsmentioning
confidence: 99%
“…9 Roots were shortened to 15 mm to standardize the length, and consequently, light distribution within the root canal during light curing, was similar to the methodology performed in previous studies. 35,36 It is possible to think that the procedure of shortening the root may have removed the cervical area, making the comparison between root thirds unfeasible. However, Galhano et al 34 demonstrated that in single-rooted teeth that were shortened to 16 mm -a value similar to that proposed in the present study, the characteristics of cervical area were still preserved, exhibiting a different morphology with increased tubule density than in the middle and apical regions.…”
Section: Discussionmentioning
confidence: 99%